2006
DOI: 10.1152/ajprenal.00081.2006
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial lesion formation is mediated by TNFR1 during neurogenic cystitis

Abstract: Interstitial cystitis (IC) is a chronic bladder inflammatory disease of unknown etiology that shares similarities with Crohn's disease and psoriasis. IC, often regarded as a neurogenic cystitis, is associated with urothelial lesions that likely compromise the bladder permeability barrier and thereby contribute to patient morbidity. Here, we use a murine model of neurogenic cystitis to investigate the mechanism of urothelial lesion formation and find that urothelial apoptosis induces formation of lesions. Lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 54 publications
5
35
0
Order By: Relevance
“…Previous studies in this same mouse model also suggest that antiTNF and anti CCL5 therapies stabilize barrier dysfunction that may otherwise contribute to heightened Cfiber activity. 15,16,39 Alternatively, temporary pain relief in IC is achieved by intravesical 2% lidocaine, and is consistent with our observa tions of lidocaineinduced pelvic pain relief in the murine IC model. 6 Figure 2 Multimodal therapy for chronic pelvic pain.…”
Section: Cortical Changes From Chronic Painsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies in this same mouse model also suggest that antiTNF and anti CCL5 therapies stabilize barrier dysfunction that may otherwise contribute to heightened Cfiber activity. 15,16,39 Alternatively, temporary pain relief in IC is achieved by intravesical 2% lidocaine, and is consistent with our observa tions of lidocaineinduced pelvic pain relief in the murine IC model. 6 Figure 2 Multimodal therapy for chronic pelvic pain.…”
Section: Cortical Changes From Chronic Painsupporting
confidence: 89%
“…14 Lamina propria mastcell accumula tion was mediated by urothelial expression of the chemokine CCL5 (previously known as RANTES) and resulted in urothelial lesions and diminished bladder-barrier function. 15,16 Because human IC symptoms are associated with lamina propria mastcell accumulation and urothelial lesions, 17,18 PRVinduced neurogenic cystitis recapitulates key aspects of the human disease, 15 suggesting the possibility of pelvic pain in PRVinduced cystitis. Indeed, PRV infected mice showed tactile hypersensitivity, or allodynia, that was specific to the pelvic region.…”
Section: Pelvic Organ Crosstalkmentioning
confidence: 99%
“…TNF-␣ and iNOS have been shown to be crucial in experimental models of other bacterial infections (20,36). In UTI, both mediators were produced in large amounts (5,30). However, a functional role in this infection has not been proven, although some studies reported partial dependence on iNOS in mice deficient for this enzyme or upon chemical inhibition of NO (26,29).…”
Section: Discussionmentioning
confidence: 99%
“…PD07I normal bladder urothelium cells were from Dr. Klumpp (Northwestern University, Chicago, IL) and cultured in EpiLife Medium (Cascade Biologics) supplemented with HKGS (Cascade Biologics) and PSA (Cascade Biologics) [24].…”
Section: Methodsmentioning
confidence: 99%